Provincial Assessment Officer Progress Report on Kumba Division (Colonial Letters and the Contact of Knowledges, 1922)
This file contains a colonial progress report on Kumba Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies